Publishing Beyond the Market : Open Access, Care, and the Commons - Samuel A. Moore (University of Michigan Press, 2025)
Publishing Beyond the Market argues that the move to open access should focus less on the free accessibility of research outputs and more on who controls the publications and infrastructures for scholarly communication. By deploying theoretical literature on science and technology studies, care ethics, and the commons, the book critically interrogates open access and reimagines a more ethical future for researcher-led publishing. A case study of Plan S—the multifunder European policy for open access publishing—explores its tendency to rehearse all the failures of commercialisation. Through critical engagement with the open access landscape, the book reveals the shortcomings of market-centric and policy-based approaches to open access book and journal publishing, particularly their tendency to reinforce conservatism, commercialism, and private control of publishing. Going forward, Publishing Beyond the Market explores the importance of collectivity and democratic governance within the transition to open access publishing. It suggests that developing a commons-based, scholar-led publishing landscape through a series of presses that are each managed by working academics could offer a productive counterpoint to marketised systems of open access and subscription publishing. In weaving themselves together in order to “scale small” these publishing initiatives would act as a counter-hegemonic project based on mutual reliance and care. By illustrating how these projects build toward a commons-based publishing future, and how they may complement other approaches to publishing within university presses and libraries, the book culminates in an argument for the infrastructures, policies, and forms of governance needed to nurture such a collective vision.